Usability evaluation of FSKM website / Lina Farhana Yahaya - Yahaya, Lina Farhana (2010)
Current Web applications are very complex and high sophisticated software products, whose usability can heavily determine their success or failure. Defining methods for ensuring usability is one of the current goals of the Web Evaluation research. Also, much attention on usability is currently paid by industry, which is recognizing the importance of adopting methods for usability evaluation before and after the application deployment. The purpose of the FSKM Web site usability test is to help the management of the Faculty to find out whether the content, navigability, and ease of information retrieval of the Web site can meet the standard and to further improve their services. The best way to find out whether the FSKM website is usable is to conduct a usability study. The purpose of this usability study is to identify the usability problems in the FSKM website by conducting an observation on numbers of clicks and time used to finish each tasks. The FSKM feedback survey was given to find out about the effectiveness, efficiency, and satisfaction from the participants. Seven test participants were assembled from the students of University Technology MARA and students which are not from University Technology MARA. For the purposes of data collection, participants' information was identified only by their test number. The tasks will perform on the FSKM Website by the respondents and the observation will be conduct. Then the questionnaires will be distributed to all students. In general, from the result and analysis, all participants' reactions to the FSKM website were negatively affected by the architecture of the site. Information related to education was not all contained within the site and is, instead, located in sub-sites representing each institute or to the Students Portal. The usability of the FSKM website is not as good as it could be and needs to be improved.